2017
DOI: 10.1371/journal.pone.0177238
|View full text |Cite
|
Sign up to set email alerts
|

Angle stability and outflow in dual blade ab interno trabeculectomy with active versus passive chamber management

Abstract: PurposeTo compare intraoperative angle stability and postoperative outflow of two ab interno trabeculectomy devices that excise the trabecular meshwork with or without active aspiration and irrigation. We hypothesized that anterior segment optical coherence tomography (AS-OCT) allows for a quantitative comparison of intraoperative angle stability in a microincisional glaucoma surgery (MIGS) pig eye training model.MethodsTwelve freshly enucleated porcine eyes were measured with AS-OCT at baseline, at the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 32 publications
4
46
0
Order By: Relevance
“…Either removing [25,26] or bypassing [21,27] these tissues can lead to a reduction in IOP. In our previous study, we characterized an ab interno goniotomy device with an active irrigation and aspiration and found that the anterior chamber depth and the nasal angle remained steady throughout the entire procedure, in contrast to a significantly lower anterior chamber stability in a passive dual blade goniotomy [12]. In the current study, we investigated the IOP-lowering efficacy of the same newly developed device in a porcine eye perfusion model and compared its performance with a plasma-mediated ablation and a passive dual blade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Either removing [25,26] or bypassing [21,27] these tissues can lead to a reduction in IOP. In our previous study, we characterized an ab interno goniotomy device with an active irrigation and aspiration and found that the anterior chamber depth and the nasal angle remained steady throughout the entire procedure, in contrast to a significantly lower anterior chamber stability in a passive dual blade goniotomy [12]. In the current study, we investigated the IOP-lowering efficacy of the same newly developed device in a porcine eye perfusion model and compared its performance with a plasma-mediated ablation and a passive dual blade.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior segment perfusion culture followed our previous protocols [12,18,19]. Briefly, within two hours of sacrifice, fresh pig eyes from a local slaughterhouse were sterilized with 5% Betadine and subsequently bisected.…”
Section: Porcine Eye Perfusion Culture Iop and Outflow Facilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The Trabectome provides active irrigation and aspiration, which maintains better stability and temperature in the anterior chamber, compared with passive chamber management [18]. No hypotony or bleb-related complications occur [10,11,19,20].…”
Section: Introductionmentioning
confidence: 99%